Hybrid Multilevel Explanation: A New Approach for Explaining Regression Models - Miranda Filho, Renato; Pappa, Gisele L. (Anais da Brazilian Conference on Intelligent Systems (BRACIS); 2023: Anais da XII Brazilian Conference on Intelligent Systems, 2023)
Regression models are commonly used to model the associations between a set of features and an observed outcome, for purposes such as prediction, finding associations, and determining causal relationships. However, interpreting the outputs of these models can be challenging, especially in complex models with many features and nonlinear interactions. Current methods for explaining regression models include simplification, visual, counterfactual, example-based, and attribute-based approaches. Furthermore, these methods often provide only a global or local explanation. In this paper, we propose a hybrid multilevel explanation (Hybrid Multilevel Explanation - HuMiE) method that enhances example-based explanations for regression models. In addition to a set of instances capable of representing the learned model, the HuMiE method provides a complete understanding of why an output is obtained by explaining the reasons in terms of attribute importance and expected values in similar instances. This approach also provides intermediate explanations between global and local explanations by grouping semantically similar instances during the explanation process. The proposed method offers a new possibility of understanding complex models and proved to be able to find examples statistically equal to or better than the main competing methods and to provide a coherent explanation with the context of the explained model.